A DINÂMICA SOCIAL CORPORATIVA EM AMBIENTES MULTICULTURAIS: UM OLHAR SOBRE O IMPACTO DA MÃO DE OBRA ESTRANGEIRA NA CULTURA E AMBIENTE ORGANIZACIONAL - Almeida, Neide Lúcia de Oliveira (2011)
At the present time cultural diversity is a crucial question for managers of corporations that internationalize their operations, look to expand their markets or, for different reasons, keep a foreigner in their functional staff. To take a look at the impact created by an expatriate professional on the organizational culture and management as well as analyze the new corporate social dynamics in multinational environments are the objectives of this study. Based on a questionnaire submitted to foreigners who work in Brazil, specifically in the city of Rio de Janeiro, a collection of information concerning their perception of questions related to the characteristics of the intrinsic cultural diversity of the players (participants) in corporate environments, analysis of the data, and interpretation of the results, the author intends to determine if the contact among persons from different cultures, who possess distinct systems of representation, can trigger a satisfactory and pleasurable relationship in the organizational environment. It is expected that the conclusion of this study should spur managers to bolster creativity, promote interaction and assimilation of the diversity by adopting new multicultural management models that include Intercultural Education in their agendas.